The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.21511/imfi.16(1).2019.17
|View full text |Cite
|
Sign up to set email alerts
|

A Markov regime switching approach to estimating the volatility of Johannesburg Stock Exchange (JSE) returns

Abstract: The study used the Markov regime switching model to investigate the presence of regimes in the volatility dynamics of the returns of JSE All-Share Index (ALSI). Volatility regimes are as a result of sudden changes in the underlying economy generating the market returns. In all, twelve candidate models were fitted to the data. Estimates from the regime switching model were compared to the industry standard non-switching GARCH (1,1) using the Deviance Information Criteria (DIC). The results show that the two-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
(27 reference statements)
0
1
2
Order By: Relevance
“…This means that the gain in the complexity of the two regime model was not enough to outdo the single regime. This result contradicts the findings of Oseifuah and Korkpoe (2019), who discovered that the two regime models outperformed the single regime models in the JSE. However, the differences may be attributed to the different sample periods.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…This means that the gain in the complexity of the two regime model was not enough to outdo the single regime. This result contradicts the findings of Oseifuah and Korkpoe (2019), who discovered that the two regime models outperformed the single regime models in the JSE. However, the differences may be attributed to the different sample periods.…”
Section: Resultscontrasting
confidence: 99%
“…However, this was not the case with the JSE stock data, where the single regime model outperformed the two regime models. This contradicts the findings of Oseifuah and Korkpoe (2019) and Makatjane and Molefe (2020) who found the single regime less effective. However, we are quick to note that we used a period that starts in 2017, whilst the studies mentioned above-considered sample periods that cover the global financial crisis of 2008.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Ardia et al [26], Oseifuah et al [27], and Xiaofei Wu et al [28] empirically showed the supremacy of the Markov-switching GARCH against non-switching GARCH models in estimating risk measures like Value-at-Risk (VaR), Expected Shortfall (ES), & left-tail distribution forecasts using financial indices. Since risk measures are better estimated by a statistical distribution that best describes the returns [11] their findings suggested that the presence of regimes in the volatility dynamics of the financial returns is prevalent.…”
Section: Literature Reviewmentioning
confidence: 99%